Heat-resistant foam sheet using destruction of cloesed cell
Patent Information
- Application Number
- KR1020230187028
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-12-20
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2043-12-20
Abstract
Description
Technology Field
[0001] The present invention relates to a heat-resistant foamed sheet that has low density and improved heat resistance by destroying closed cells. Background Technology
[0002] Low-density foam sheets can be defined as having a density of approximately 500 kg / m³ or less. If the cell size of the low-density foam sheet is approximately 500 μm or less, the moldability may be poor, warping or cracking may occur, and heat resistance may be reduced. The problem to be solved
[0003] Accordingly, the objective of the present invention is to provide a low-density heat-resistant foam sheet with good moldability, no bending or cracking, and improved heat resistance, and a method for manufacturing the same. means of solving the problem
[0004] To achieve the above-mentioned objective, the present invention provides a foamed sheet formed from a polyester resin composition and comprising open cells formed by breaking closed cells.
[0005] In the present invention, the density of the foam sheet may be 500 kg / m³ or less.
[0006] In the present invention, the cell size of the foam sheet may be 600 μm or less.
[0007] In the present invention, the light transmittance of the foamed sheet may be 1% or more.
[0008] In the present invention, the foam sheet may include holes formed on the surface by the destruction of closed cells.
[0009] In the present invention, the number of holes in the foam sheet may be 10 or more per area of 0.16 mm².
[0010] In the present invention, the height of the foam sheet falling from the flat surface due to bending occurring during the heat resistance test of the foam sheet under conditions of 200°C and 30 seconds may be 1 mm or less.
[0011] In the present invention, the rate of change in thickness before and after the heat resistance test of the foam sheet under conditions of 200°C and 30 seconds may be 100% or less.
[0012] In the present invention, the polyester resin composition may include a polyester resin, a thickener, a nucleating agent, and a foaming agent.
[0013] In the present invention, the polyester resin may be polyethylene terephthalate (PET) resin.
[0014] In the present invention, the intrinsic viscosity (IV) of the polyester resin may be 0.65 dL / g or higher.
[0015] In the present invention, the molecular ratio of a polyester resin with a molecular weight of 10,000 or more may be 60% by weight or more based on the total weight of the polyester resin.
[0016] In the present invention, the content of the thickener may be 1% by weight or more based on the total weight of the composition.
[0017] In the present invention, the content of the nucleating agent may be 1% by weight or more based on the total weight of the composition.
[0018] In the present invention, the particle size of the nucleating agent may be 8 μm or less.
[0019] In addition, the present invention provides a method for manufacturing a foamed sheet comprising the steps of: forming a foamed sheet with a polyester resin composition; and breaking closed cells to form open cells.
[0020] In the present invention, open cells can be formed by destroying closed cells through needle punching.
[0021] In the present invention, the needle may be a needle without a hook.
[0022] In the present invention, the thickness of the needle may be 0.2 to 2.5 mm.
[0023] In the present invention, needles can be arranged at intervals of 5,000 to 10,000 / 5,000 cm². Effects of the invention
[0024] The foamed sheet according to the present invention is a low-density, heat-resistant foamed sheet having low density and improved heat resistance. By destroying closed cells and forming open cells through needle punching, the moldability of the foamed sheet is good, no bending or cracking occurs, and heat resistance can be improved. Specific details for implementing the invention
[0025] The present invention will be described in detail below.
[0026] The present invention relates to a low-density heat-resistant foamed sheet utilizing closed-cell destruction. The foamed sheet according to the present invention is formed from a polyester resin composition and may include open cells formed by destroying closed cells.
[0027] In the present invention, cell expansion (secondary foaming) at high temperatures can be controlled due to the partial destruction of closed cells through needle punching, and accordingly, warping control and heat resistance after processing can be improved. The foamed sheet must not change in thickness after prolonged exposure to heat, and can prevent post-foaming by providing gas passages through needle punching. In addition, gas within the foamed sheet can be removed through the open cells.
[0028] The foamed sheet according to the present invention comprises both closed cells and open cells, and the cells initially formed (manufactured) are mostly closed cells, and through post-processing (needle punching), a portion of the closed cells forms open cells.
[0029] The density of the foam sheet may be, for example, 500 kg / m³ or less, 450 kg / m³ or less, 400 kg / m³ or less, 350 kg / m³ or less, 300 kg / m³ or less, 250 kg / m³ or less, or 200 kg / m³ or less, taking into account physical properties such as lightness and rigidity; it may also be 50 kg / m³ or more, 100 kg / m³ or more, or 150 kg / m³ or more; for example, it may be 100 to 500 kg / m³, or 150 to 450 kg / m³. Thus, the foam sheet according to the present invention may be a low-density foam sheet that takes into account physical properties such as lightness.
[0030] The thickness of the foam sheet may be, for example, 1 mm or more, 1.5 mm or more, 2 mm or more, 2.5 mm or more, or 3 mm or more, taking into account physical properties such as lightness and rigidity; it may also be 10 mm or less, 9 mm or less, 8 mm or less, 7 mm or less, 6 mm or less, or 5 mm or less; for example, it may be 1 to 10 mm, 1 to 5 mm, or 1.5 to 3 mm.
[0031] The cell size of the foam sheet may be, for example, 600 μm or less, 500 μm or less, 450 μm or less, 400 μm or less, 350 μm or less, 300 μm or less, or 250 μm or less, taking into consideration physical properties such as moldability, lightness, heat resistance, and rigidity; it may also be 50 μm or more, 100 μm or more, 150 μm or more, or 200 μm or more; for example, it may be 50 to 600 μm, 100 to 500 μm, or 200 to 500 μm. If the cell size of the foam sheet is too large, the moldability may be poor. The cell size may refer to the average cell size, and specifically, it may refer to the average value of the lengths of the major and minor axes calculated after measuring the lengths of the major and minor axes of the cell using a scanning electron microscope (SEM), etc.
[0032] The light transmittance of the foam sheet may be 1% or more, 1.5% or more, 2% or more, 4% or more, 6% or more, 8% or more, 10% or more, or 12% or more; it may also be 20% or less, 18% or less, 16% or less, or 14% or less; for example, it may be 1 to 20%, 1.5 to 15%, or 2 to 13%. Compared to a foam sheet containing only closed cells, the light transmittance of the foam sheet may be increased by forming a plurality of open cells and surface holes in the foam sheet by needle punching. Through such transmittance measurement, the formation of open cells and surface holes and the degree of such formation can be evaluated.
[0033] The foam sheet may include a number of holes formed on the surface by the destruction of closed cells. The number of holes formed on the surface of the foam sheet may be 10 or more, 20 or more, 30 or more, or 40 or more per an area of 0.16 mm²; it may also be 80 or fewer, 70 or fewer, 60 or fewer, or 50 or fewer; for example, it may be 10 to 80, 20 to 70, 30 to 60, or 40 to 50. The number of surface holes can be obtained by observing the surface magnified by about 50 times using an optical microscope and counting the number of holes within an area of 0.16 mm². Through the measurement of the number of surface holes in this way, the presence and degree of formation of open cells can also be evaluated.
[0034] The height of the foam sheet detached from the flat surface due to bending occurring during a heat resistance test of the foam sheet at 200°C and 30 seconds may be 1 mm or less, 0.5 mm or less, 0.3 mm or less, 0.1 mm or less, or 0 mm. When performing a heat resistance evaluation, the foam sheet may bend; in this case, a part of the foam sheet does not touch (contact with) the flat surface (such as the ground) and remains floating away from the flat surface. The more bending occurs, the greater the height of the sheet floating away from the flat surface. In this case, the height may refer to the highest height furthest from the flat surface. Since the foam sheet according to the present invention has improved heat resistance, no bending may occur at all, that is, the height may be 0 mm.
[0035] The rate of change in thickness before and after a heat resistance test of a foamed sheet under conditions of 200°C and 30 seconds may be 100% or less, 80% or less, 60% or less, 50% or less, 40% or less, 30% or less, 20% or less, or 15% or less; it may also be 0% or more, 1% or more, 2% or more, 3% or more, or 4% or more; for example, it may be 1 to 100%, 2 to 50%, 3 to 20%, or 4 to 15%. Thus, the foamed sheet according to the present invention can exhibit improved heat resistance by having a low rate of change in sheet thickness (%) before and after the heat resistance evaluation.
[0036] As such, the foamed sheet according to the present invention is a low-density (150 to 500 kg / m³) sheet, and is a sheet with improved heat resistance (200°C × 30 seconds) by destroying closed cells, and may be a foamed sheet with increased transmittance, improved bending after heat treatment, and improved heat resistance.
[0037] The foam sheet has a first surface (e.g., an upper surface) and a second surface (e.g., a lower surface), and optionally, a composite material with a multilayer structure can be formed by additionally laminating another layer, such as a back surface layer, a coating layer, a resin layer, a fiber layer, and / or an adhesive layer, on the first surface and / or the second surface as needed.
[0038] The raw material of the foam sheet may be a polyester resin composition, and the polyester resin composition may include a polyester resin, a thickener, a nucleating agent, and a foaming agent.
[0039] The polyester resin may be a polyethylene terephthalate (PET) resin as a main component, preferably. By using PET resin, it can be environmentally friendly and easy to reuse. To improve physical properties, the PET resin used in the foamed sheet may be a PET resin having a specific range for intrinsic viscosity, molecular weight, molecular weight distribution, and / or melting point.
[0040] The intrinsic viscosity (IV) of the PET resin may be, for example, 0.65 dL / g or more, 0.7 dL / g or more, 0.72 dL / g or more, 0.74 dL / g or more, or 0.76 dL / g or more; it may also be 1.0 dL / g or less, 0.95 dL / g or less, 0.9 dL / g or less, 0.85 dL / g or less, or 0.82 dL / g or less, for example, 0.65 to 1 dL / g, 0.7 to 0.95 dL / g, 0.72 to 0.9 dL / g, 0.74 to 0.85 dL / g, or 0.76 to 0.82 dL / g. If the intrinsic viscosity (IV) of the PET resin is too low, the cell size of the foam sheet increases, and moldability may be poor.
[0041] The weight-average molecular weight (Mw) of the PET resin may be 20,000 to 200,000, 50,000 to 150,000, or 60,000 to 100,000. The weight-average molecular weight can be measured by gel permeation chromatography (GPC, analytical instrument HLC-8320), and polymethyl methacrylate (PMMA) may be used as a standard sample. The unit of molecular weight may be g / mol or Da.
[0042] In particular, the PET resin may be a PET resin in which the proportion of molecules with a molecular weight of 10,000 or more, indicated by the fine molecular weight distribution, accounts for 60% or more of the total weight of the PET resin. That is, the proportion of molecules with a molecular weight of 10,000 or more in the PET resin may be 60% or more of the total weight of the PET resin, and the proportion of molecules with a molecular weight of less than 10,000 may be less than 40% of the total weight. The proportion of molecules with a molecular weight of 10,000 or more may be 60% or more, 65% or more, or 70% or more of the total weight; and may also be 100% or less, 95% or less, 90% or less, 85% or less, 80% or less, or 75% or less of the total weight; for example, it may be 60 to 100%, 65 to 90%, or 70 to 80% of the total weight. If the proportion of molecules with a molecular weight of 10,000 or more is too low, the cell size of the foamed sheet increases, and the moldability may be poor.
[0043] The differential molecular weight distribution is one of the methods of expressing the molecular weight distribution of polymeric substances, and the differential molecular weight distribution curve is a curve that expresses the amount of a substance with molecular weight M in g as a function of M.
[0044] The melting point of the PET resin may be 250°C or higher, 253°C or higher, or 256°C or higher; it may also be 300°C or lower, 290°C or lower, 280°C or lower, 270°C or lower, or 260°C or lower, for example, 250 to 300°C, 253 to 280°C, or 256 to 270°C.
[0045] Preferably, the PET resin may be a PET resin that satisfies at least two of the above-described properties, namely, an intrinsic viscosity (IV) of 0.65 dL / g or more, preferably 0.76 to 0.82 dL / g, and also has a molecular weight distribution of 10,000 or more, which is the proportion of molecules with a molecular weight of 60% or more of the total weight of the PET resin.
[0046] Particularly preferably, the PET resin may be a PET resin that simultaneously satisfies all of the above-described properties, namely having an intrinsic viscosity (IV) of 0.65 dL / g or more, a weight average molecular weight of 20,000 or more, and a molecular weight distribution of 10,000 or more, which accounts for 60% or more of the total weight of the PET resin, and a melting point of 250°C or more.
[0047] When using a PET resin having these physical properties, a cold-formed part can pass through an 80°C heat resistance cycle. The heat resistance cycle can be evaluated by maintaining the molded part in the same state as an actual car, performing 3 cycles with the following conditions as 1 cycle, observing the appearance, and determining whether there is a change in shape. The heat resistance cycle may consist of a step of standing at 80±2°C for 3 hours, 23±2°C for 1 hour, -30±2°C for 3 hours, 23±2°C for 1 hour, 50±2°C for 15 hours at 95~100% relative humidity (RH), and 23±2°C for 1 hour.
[0048] Thickeners are added to control the melt viscosity, melt strength, etc., of the foamed composition, and examples include pyromellitic acid dianhydride (PMDA) and epoxy.
[0049] The content of the thickener may be, for example, 1 to 5 weight%, 1 to 4 weight%, or 2 to 3.5 weight% based on the total weight of the composition. If the content of the thickener is too low, foaming may not occur, and the density of the foamed sheet may increase. Even if the content of the thickener is too high, particularly 5 weight% or more, there may be no further change in melt viscosity, etc.
[0050] Nucleating agents are added to control cell density, and inorganic compounds such as talc, calcium carbonate, mica, silica, diatomaceous earth, alumina, titanium oxide, zinc oxide, magnesium oxide, magnesium hydroxide, aluminum hydroxide, calcium hydroxide, potassium carbonate, magnesium carbonate, potassium sulfate, barium sulfate, sodium bicarbonate, and glass beads may be used.
[0051] The content of the nucleating agent may be, for example, 1 to 10 weight%, 1.5 to 4 weight%, or 2 to 3.5 weight% based on the total weight of the composition. If the content of the nucleating agent is too low, heat resistance, etc., may be reduced, cell density may be lowered, and surface roughness may be poor. If the content of the nucleating agent is too high, wrinkles may occur on the surface of the sheet.
[0052] The particle size of the nucleating agent may be, for example, 1 to 8 μm, 2 to 6 μm, or 3 to 4 μm. If the particle size of the nucleating agent is too large, the cell size may increase, and heat resistance and moldability may decrease.
[0053] A blowing agent is added to foam the composition and control the density of the foamed sheet, and may be used as: gases such as N2, CO2, and Freon; physical blowing agents such as pentane, butane, propane, neopentane, hexane, isohexane, heptane, isoheptane, and methyl chloride; and chemical blowing agents such as azodicarbonamide compounds, P,P'-oxybis(benzenesulfonylhydrazide) compounds, and N,N'-dinitrosopentamethylenetetraamine compounds.
[0054] The content of the foaming agent may be, for example, 0.1 to 5 parts by weight, 0.5 to 4 parts by weight, or 1 to 3 parts by weight based on 100 parts by weight of the resin.
[0055] In addition, the raw materials of the foam sheet may additionally include surfactants, UV blockers, hydrophilizing agents, flame retardants, heat stabilizers, waterproofing agents, cell size expanders, infrared dampeners, plasticizers, fire-retardant chemicals, pigments, elastomers, extrusion aids, antioxidants, fillers, anti-aircraft agents, UV absorbers, etc., for the purpose of imparting hydrophilicity, waterproofing, flame-retardant, and UV-blocking functions.
[0056] In addition, the present invention provides a method for manufacturing a foamed sheet comprising the steps of: forming a foamed sheet with a polyester resin composition; and breaking closed cells to form open cells.
[0057] The formation step of the foamed sheet can be performed through extrusion foaming. Extrusion foaming simplifies process steps and enables mass production by continuously extruding and foaming the melted resin. Furthermore, it prevents cracking between beads and granular fracture during bead foaming, thereby enabling the realization of superior compressive strength.
[0058] The step of forming open cells can be performed by destroying closed cells through needle punching to form open cells. That is, as a post-processing step, open cells can be formed by needle punching the foamed sheet. Needle punching can be performed over the entire thickness of the foamed sheet or on a portion of its thickness.
[0059] The needles used for needle punching may be hookless needles. The thickness of the needles may be, for example, 0.2 to 2.5 mm, 0.5 to 2.2 mm, 0.8 to 2 mm, 1.1 to 1.8 mm, or 1.3 to 1.7 mm. The spacing of the needles may be, for example, 5,000 to 10,000 needles / 5,000 cm², 6,000 to 9,000 needles / 5,000 cm², or 7,000 to 8,000 needles / 5,000 cm².
[0060] The foamed sheet according to the present invention can be applied to applications requiring heat resistance, such as automobiles, building materials, and back sheets for electronic products.
[0061] The present invention will be explained in more detail below with reference to examples.
[0062] [Examples and Comparative Examples]
[0063] A PET foam sheet was prepared using a PET resin having the viscosity and molecular weight distribution shown in Tables 1 and 2, a thickener and a foaming agent with the content shown in Tables 1 and 2, and a nucleating agent with the content and particle size shown in Tables 1 and 2.
[0064] Next, as a post-processing step, the manufactured PET foam sheet was needle-punched to destroy some of the closed cells and form open cells. At this time, the needle punching was performed using hookless needles with a thickness of 1.5 mm and a spacing of 7,500 / 5,000 cm².
[0065] The physical properties of the needle-punched PET foam sheets are shown in Tables 1 and 2.
[0066] The method for measuring physical properties is as follows.
[0067] (1) Intrinsic viscosity (IV)
[0068] The intrinsic viscosity was measured at 35°C using an Uwerod viscometer by dissolving the sample in a mixed solution of phenol and tetrachloroethane (mixing ratio = 1:1 volume ratio) at a concentration of 0.5 wt%.
[0069] (2) Molecular weight
[0070] The molecular weight was measured at 254 nm using gel permeation chromatography (GPC, analytical instrument HLC-8320) after dissolving the sample in a mixed solution of chloroform and phenol (mixing ratio = 1:1 volume ratio). PMMA was used as the standard sample.
[0071] (3) Density
[0072] Density was measured using Alfa Mirage’s EW-300SG under KS M ISO 845 conditions.
[0073] (4) Cell size
[0074] The cell size was determined by measuring the lengths of the major and minor axes of the cell using a scanning electron microscope (SEM) and taking the average value.
[0075] (5) Light transmittance
[0076] Light transmittance was measured at a wavelength of 350 nm using an ultraviolet-visible spectrophotometer (UV-Vis) instrument.
[0077] (6) Number of surface holes
[0078] The number of surface holes was obtained by observing the surface with an optical microscope magnified about 50 times and counting the number of holes within an area of 0.16 mm².
[0079] (7) Bending
[0080] Flexure was evaluated by measuring the maximum height of the foam sheet floating above the plane without touching the plane after heat-treating the foam sheet at 200°C for 30 seconds.
[0081] (8) Heat resistance
[0082] Heat resistance was evaluated by heat-treating the foamed sheet at 200°C for 30 seconds and measuring the rate of change in thickness of the foamed sheet before and after heat treatment.
[0083] (9) Moldability
[0084] Moldability was evaluated by thermoforming a foamed sheet so that the ratio of height (H) to diameter (D) (H / D) was 0.5, and then visually checking for the occurrence of bursting and the contour of the molded product.
[0085] division Example 1 Example 2 Example 3 PET resin Intrinsic viscosity (IV) ㎗ / g 0.8 0.8 0.8 Molecular weight of 10,000 or more % 72 72 72 Thickener PMDA wt% 2.5 2.7 2.9 blowing agent Hydrocarbons (pentane, butane, propane) wt% 0~5 0~3 0~3 Nucleus agent Inorganic nucleating agent (CaCO3, talc) wt% 3 3 3 particle size ㎛ 3 3 3 Needle punching process ○ ○ ○ PET foam sheet density kg / ㎥ 150 300 450 thickness ㎜ 3.0 1.5 2.2 Average cell size ㎛ 200~500 200~500 200~500 Light transmittance % 2.17 4.74 12.2 Number of surface holes (×50) ea 40~45 40~45 40~45 Physical properties Bending (200℃, 30 seconds) ㎜ 0 0 0 Heat resistance (200℃, 30 seconds) % 6.7 13.3 4.5 Formability (H / D 0.5 thermoforming) - Good Good Good
[0086] division Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 PET resin Intrinsic viscosity (IV) ㎗ / g 0.6 0.8 0.8 0.8 Molecular weight of 10,000 or more % 50 72 72 72 Thickener PMDA wt% 2.5 0.5 2.5 2.5 blowing agent Hydrocarbons (pentane, butane, propane) wt% 0~5 0~5 0~5 0~5 Nucleus agent Inorganic nucleating agent (CaCO3, talc) wt% 3 3 3 3 particle size ㎛ 3 3 10 3 Needle punching process ○ ○ ○ × PET foam sheet density kg / ㎥ 150 Foaming × 150 150 thickness ㎜ 3 3.0 3.0 Average cell size ㎛ 800~1000 400~700 200~500 Light transmittance % 5 5 0.1 Number of surface holes (×50) ea 40~45 40~45 0 Physical properties Bending (200℃, 30 seconds) ㎜ 0 0 2 Heat resistance (200℃, 30 seconds) % 10 10 133 Formability (H / D 0.5 thermoforming) - error error Good
[0087] According to Tables 1 and 2, in the case of the example, a PET foam sheet was prepared using a PET resin having appropriate viscosity and molecular weight distribution, an appropriate amount of thickener and foaming agent, and an appropriate amount and particle size of nucleating agent, and then needle punched; thereby, a foam sheet having appropriate density, appropriate thickness, appropriate cell size, appropriate light transmittance, appropriate number of surface holes, improved bending, improved heat resistance, and good moldability could be obtained.
[0088] However, in the case of Comparative Example 1, because a PET resin with low viscosity and a low proportion of molecular weights of 10,000 or more was used, the cell size increased and the moldability was poor.
[0089] In addition, in the case of Comparative Example 2, since the thickener content was low, foaming did not occur and a foamed sheet was not formed.
[0090] In addition, in the case of Comparative Example 3, the cell size increased and moldability was poor because the particle size of the nucleating agent was large.
[0091] In addition, in the case of Comparative Example 4, since needle punching was not performed, open cells were not formed, and consequently, light transmittance was low, surface holes were not formed, warping occurred, and heat resistance was significantly reduced.
Claims
Claim 1 A foamed sheet formed from a polyester resin composition and comprising open cells formed by destroying closed cells, wherein the light transmittance of the foamed sheet is 1% or more, the foamed sheet comprises holes formed on the surface by the destruction of closed cells, and the number of holes in the foamed sheet is 10 or more per area of 0.16 mm², and the polyester resin composition comprises a polyester resin, a thickener, a nucleating agent, and a foaming agent, and the molecular ratio of the polyester resin having a molecular weight of 10,000 or more is 60% by weight or more based on the total weight of the polyester resin. Claim 2 In paragraph 1, a foam sheet having a density of 500 kg / ㎥ or less. Claim 3 In claim 1, the foam sheet has a cell size of 600 μm or less. Claim 4 delete Claim 5 delete Claim 6 delete Claim 7 A foam sheet according to claim 1, wherein the height of the foam sheet falling from the flat surface due to bending occurring during a heat resistance test of the foam sheet under conditions of 200°C and 30 seconds is 1 mm or less. Claim 8 A foamed sheet according to claim 1, wherein the rate of change in thickness before and after a heat resistance test under conditions of 200°C and 30 seconds is 100% or less. Claim 9 delete Claim 10 In paragraph 1, the polyester resin is a polyethylene terephthalate resin, a foamed sheet. Claim 11 A foamed sheet according to claim 1, wherein the intrinsic viscosity of the polyester resin is 0.65 dL / g or higher. Claim 12 delete Claim 13 A foamed sheet according to claim 1, wherein the content of the thickener is 1% by weight or more based on the total weight of the composition. Claim 14 A foamed sheet according to claim 1, wherein the content of the nucleating agent is 1% by weight or more based on the total weight of the composition. Claim 15 A foamed sheet according to claim 1, wherein the particle size of the nucleating agent is 8 μm or less. Claim 16 A method for manufacturing a foamed sheet according to claim 1, comprising the steps of: forming a foamed sheet with a polyester resin composition; and breaking closed cells to form open cells. Claim 17 In claim 16, a method for manufacturing a foamed sheet by destroying closed cells through needle punching to form open cells. Claim 18 In paragraph 17, a method for manufacturing a foam sheet in which the needle is a hookless needle. Claim 19 A method for manufacturing a foamed sheet according to claim 17, wherein the thickness of the needles is 0.2 to 2.5 mm. Claim 20 In claim 17, a method for manufacturing a foamed sheet in which needles are arranged at intervals of 5,000 to 10,000 / 5,000 cm².
Citation Information
Patent Citations
PET open-cell foam material and preparation method thereof
CN116178911A
A cellular thermoplastic polymer foam and a process for preparing the same
KR1020010075181A
Sound Blocking Material For Vehicle Containing Polyester Foam Sheet
KR1020190025337A
Polyester foam sheet and manufacturing method of the same
KR1020210087163A